Adaptation to Industrial Stressors Through Genomic and Transcriptional Plasticity in a Bioethanol Producing Fission Yeast Isolate. Issue 4 (1st April 2020) - Vassiliadis, Dane; Wong, Koon Ho; Blinco, Jo; Dumsday, Geoff; Andrianopoulos, Alex; Monahan, Brendon
Abstract: Schizosaccharomyces pombe is a model unicellular eukaryote with ties to the basic research, oenology and industrial biotechnology sectors. While most investigations into S. pombe cell biology utilize Leupold's 972 h - laboratory strain background, recent studies have described a wealth of genetic and phenotypic diversity within wild populations of S. pombe including stress resistance phenotypes which may be of interest to industry. Here we describe the genomic and transcriptomic characterization of Wilmar-P, an S. pombe isolate used for bioethanol production from sugarcane molasses at industrial scale. Novel sequences present in Wilmar-P but not in the laboratory S. pombe genome included multiple coding sequences with near-perfect nucleotide identity to Schizosaccharomyces octosporus sequences. Wilmar-P also contained a ∼100kb duplication in the right arm of chromosome III, a region harboring ght5 +, the predominant hexose transporter encoding gene. Transcriptomic analysis of Wilmar-P grown in molasses revealed strong downregulation of core environmental stress response genes and upregulation of hexose transporters and drug efflux pumps compared to laboratory S. pombe . Finally, examination of the regulatory network of Scr1, which is involved in the regulation of several genes differentially expressed on molasses, revealed expanded binding of this transcription factor in Wilmar-P compared to laboratory S. pombe in the molasses condition. Together our results point to both genomic plasticity and transcriptomic adaptation as mechanisms driving phenotypic adaptation of Wilmar-P to the molasses environment and therefore adds to our understanding of genetic diversity within industrial fission yeast strains and the capacity of this strain for commercial scale bioethanol production.